The effect of combined strength training on vertical jump performance in young basketball players: A systematic review and meta-analysis - Uysal, H. S.; Dalkiran, O.; Korkmaz, S.; Akyildiz, Z.; Nobari, H.; Clemente, F. M. (Strength and Conditioning Journal, 2023)
Combined strength training is performed with a combination of plyometric exercises and traditional strength exercises. This training method with different protocols (such as complex training or contrast training) is used to develop vertical jump performance in basketball. Combined strength training is based on the theory of PAP, and physiological changes in the nervous musculature allow for acute performance enhancement. Included and excluded studies were determined according to PICOS criteria. The search was performed on the electronic databases of Google Scholar, PubMed, and Scopus between September 1-7, 2022. The effect of combined strength training on vertical jump performance in basketball was compared with different training methods and as a result, a moderate effect was found in favor of combined strength training (ES=1.11, (95%CI 0.63-1.60), I2= 82%). As a result of systematic review and meta-analysis, it has been found that combined strength training applied in different forms in basketball is superior to other training methods in improving vertical jump performance. On the other hand, there is no superiority between the combined strength training protocols. Athletic performance specialists may improve jump performance by combining plyometric and traditional strength exercises in the same training season.